Exploring the degree of nicotine dependence and willingness to quit smoking in Chinese smoking patients with stroke: A cross-sectional survey. Issue 49 (10th December 2021) - Li, Ling; Li, Haifeng; Zhang, Ying; Zheng, Chengyuan; Xu, Houyun; Cheng, Zizhen
Abstract : Abstract: Smoking is closely related to the occurrence of stroke. The degree of nicotine dependence and willingness to quit smoking are key factors that determine whether a smoker can successfully quit smoking. Few studies have been conducted on factors affecting the willingness to quit smoking among smokers who suffered from stroke. Although the smoking rate has declined, it is still the main changeable risk factor for cerebrovascular diseases. We aimed to investigate the current status of nicotine dependence and willingness to quit smoking among patients who suffered from stroke. We also clarified factors that affect the willingness to quit smoking among stroke patients and provide evidence for quitting smoking. Convenience sampling methods were used to conduct cross-sectional studies. A questionnaire survey was administered to 215 stroke patients who smoked. A general information questionnaire as well as patient smoking and cessation status questionnaire were used. Nicotine dependence test scale, smoking attitude factor score, and tobacco harm perception scale were applied for investigation. Logistic regression was used to analyze factors related to patients' willingness to quit smoking. Statistically significant differences in willingness to quit smoking were found among stroke patients with different ages, household registration status, education levels, marital status, occupation, smoking attitude, and nicotine dependence ( P < .05). About 34.4%, 39.1%, and 26.5% of smoking patients had low, moderate, and severe nicotine dependence, respectively. Logistic analysis showed that compared with other occupations, workers, retirees, farmers, and freelancers compared with other people (0.050, 0.081, 0.053, 0.048) had a negative impact on the willingness to quit smoking among stroke patients. Compared with positive attitudes, negative and neutral smoking attitudes (0.190, 0.048) had a negative impact on the willingness to quit smoking among stroke patients. Compared with high nicotine dependence, low and moderate nicotine dependence (4.628, 2.596) had a positive impact on willingness to quit smoking. Smoking patients in neurology department are more willing to quit smoking (67.9%). Factors such as occupation, smoking attitude, and nicotine dependence should be considered when establishing smoking cessation interventions for stroke smokers.